Educational preparation and other individual related factors associated with performance of specific functions of practicing nurses in different work settings - Dumlao, Josefina Fanuncial
This study identified the professional activities of practicing nurses as reported by 258 randomly selected nurses from four work settings in Metro Manila and Nueva Vizcaya's hospital, school, industry and public health agencies and determined how selected individual-, work-, and education-related factors influence the performance of nursing functions and activities. Nurses who practice in hospitals perform more frequently 22 of the Uniquely-Nursing functions, 6 to 8 Delegated and 7 of the 13 Nursing-Related functions as compared with non-hospital nurses. These functions are mainly individualized nursing care given to the sick. No significant relationship was found between nursing degree completed and involvement in activities that promote professional growth.